The Hyperlipidaemic Drug Fenofibrate Significantly Reduces Infection by SARS-CoV-2 in Cell Culture Models - Davies, Scott P.; Mycroft-West, Courtney J.; Pagani, Isabel; Hill, Harriet J.; Chen, Yen-Hsi; Karlsson, Richard; Bagdonaite, Ieva; Guimond, Scott E.; Stamataki, Zania; De Lima, Marcelo Andrade; Turnbull, Jeremy E.; Yang, Zhang; et al. (Frontiers in pharmacology, 2021)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic has caused a significant number of fatalities and worldwide disruption. To identify drugs to repurpose to treat SARS-CoV-2 infections, we established a screen to measure the dimerization of angiotensin-converting enzyme 2 (ACE2), the primary receptor for the virus. This screen identified fenofibric acid, the active metabolite of fenofibrate. Fenofibric acid also destabilized the receptor-binding domain (RBD) of the viral spike protein and inhibited RBD binding to ACE2 in enzyme-linked immunosorbent assay (ELISA) and whole cell-binding assays. Fenofibrate and fenofibric acid were tested by two independent laboratories measuring infection of cultured Vero cells using two different SARS-CoV-2 isolates. In both settings at drug concentrations, which are clinically achievable, fenofibrate and fenofibric acid reduced viral infection by up to 70%. Together with its extensive history of clinical use and its relatively good safety profile, this study identifies fenofibrate as a potential therapeutic agent requiring an urgent clinical evaluation to treat SARS-CoV-2 infection.